1997
DOI: 10.3109/17518429709025849
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural sequelae following cranial irradiation and chemotherapy in children: an analysis of risk factors

Abstract: Neurobehavioural deficits are commonly reported following treatment for childhood cancers. This study examined the impact of cranial irradiation (CRT) and chemotherapy in children, aiming to identify factors detrimental to long-term outcome. The study compared survivors of acute lymphoblastic leukemia (ALL), treated with CRT and chemotherapy (CRT group: n = 100), survivors of cancers treated with chemotherapy only (n = 50) and healthy controls (n = 100) for intelligence, academic achievement, information proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 59 publications
4
56
1
1
Order By: Relevance
“…CRT is associated with poor educational outcomes among survivors of childhood cancer, 24,27,28 as we also demonstrated in the current study. Reports have indicated that IT MTX is a risk factor for poor cognitive performance and neurologic function.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…CRT is associated with poor educational outcomes among survivors of childhood cancer, 24,27,28 as we also demonstrated in the current study. Reports have indicated that IT MTX is a risk factor for poor cognitive performance and neurologic function.…”
Section: Discussionsupporting
confidence: 85%
“…Younger age at diagnosis and/or treatment 7,14,[24][25][26] ; cranial or craniospinal radiotherapy (CRT) and/or intrathecal methotrexate (IT MTX) 15,24,25,[27][28][29] ; higher therapeutic doses of CRT or IT MTX 17,24 ; and diagnoses of central nervous system (CNS) tumors, leukemia (particularly acute lymphoblastic leukemia [ALL]), Hodgkin lymphoma, or neuroblastoma 13,15,30 as well as being female, [30][31][32][33] of lower socioeconomic status (SES), 20 and having a longer time since diagnosis 24 have been reported to be associated with an increased risk of poorer educational outcomes. Previous studies have not always assessed the potential confounding effects of missed school, 34 SES, 35 and physical health or physical impairments.…”
mentioning
confidence: 99%
“…Moreover, our patient sample is heterogeneous in terms of tumor type and radiation dose. However, when tumor variables are controlled for, CRT is more associated with declines in processing speed, IQ, and working memory performance than surgery-only or surgery and chemotherapy treatment in pediatric posterior fossa tumor populations (Anderson et al, 1997;Schatz et al, 2000b;Langer et al, 2002). Brain-based explanations for CRT-related behavioral delays in information-processing speed include radiationinduced mechanical disruptions in relaying neural signals such as injury to existing white matter that modulates conduction times and synchrony of impulse conduction (Fields, 2008a,b) or damage to glial progenitor cells that regulate future myelination and neurotransmitter functions that are important for neural transmission (Monje et al, 2002;Dietrich and Kempermann, 2006;Roy et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, the neural mechanisms of impaired information processing, a core deficit after many forms of brain injury (Anderson and Arciniegas, 2010;Dockree and Robertson, 2011;Padovani et al, 2012;, are unclear. We propose that gamma oscillations may be an excellent marker of cognitive health and impairment in children.…”
Section: Introductionmentioning
confidence: 99%
“…7,13 In addition, long-term difficulties in cognitive and academic function are often described, 22 most frequently visual perceptual, attention, and math skills. 10,13,[23][24][25][26][27][28][29][30][31][32][33][34][35] Voxel-based morphometry (VBM) is an automated method for analyzing whole brain regional differences on a voxel-by-voxel basis. The purpose of this study was to use VBM to examine regional white and gray matter differences in a group of long-term survivors of ALL treated with systemic and intrathecal chemotherapy, compared with a group of healthy controls, and to examine the relationship of regional brain volumes to cognitive function.…”
mentioning
confidence: 99%